2010
DOI: 10.1007/s10461-010-9666-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Stress and Social Network Characteristics Among HIV-Positive Latino and African American Women and Men Who have Sex with Men

Abstract: Social support and stress have been poorly characterized for persons with HIV, particularly for racial/ethnic minorities. To address this gap, data on general and HIV-specific support and stress and social network characteristics were collected for 399 African American and Latino women and men who have sex with men (MSM) in Los Angeles County. African American (mean = 41; SD = 17) and Latina (mean = 40; SD = 19) women reported the highest general support. Stress was also highest for Latina women (mean = 18; SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 34 publications
1
40
1
1
Order By: Relevance
“…Our stress/ retention in care finding is consistent with a study of a general rural primary health care clinic population in which high self-reported family stress was associated with medical follow-up, referrals and/or hospitalization, and high severity of illness while controlling for support, age, gender and race [4]. The data from the current study and our prior analysis suggest that African American MSM may be more likely to rely on support from providers and seek HIV care in part to cope with the stress they experience from their social network members [18] or it is possible that ''positive nagging'' by social network members to take care of an illness results in more care visits. The lack of an association between the SRSQ general and HIV-specific support measures and retention in care is an unexpected finding.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Our stress/ retention in care finding is consistent with a study of a general rural primary health care clinic population in which high self-reported family stress was associated with medical follow-up, referrals and/or hospitalization, and high severity of illness while controlling for support, age, gender and race [4]. The data from the current study and our prior analysis suggest that African American MSM may be more likely to rely on support from providers and seek HIV care in part to cope with the stress they experience from their social network members [18] or it is possible that ''positive nagging'' by social network members to take care of an illness results in more care visits. The lack of an association between the SRSQ general and HIV-specific support measures and retention in care is an unexpected finding.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, our data suggest that African American MSM may adhere to their HIV care visits in part due to the support received from their HIV provider that includes a positive social interaction that they may not experience in other domains of their lives [6]. In fact, in a previous report on these data, African American MSM reported the highest HIV-specific support scores from their providers compared to family, friends, and others as well as relatively high satisfaction with the support received from providers [18]. Our stress/ retention in care finding is consistent with a study of a general rural primary health care clinic population in which high self-reported family stress was associated with medical follow-up, referrals and/or hospitalization, and high severity of illness while controlling for support, age, gender and race [4].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both of these results demonstrated the importance of instrumental support to a woman's sense of being supported, either by family (when bedridden) or friends (with housework). Other researchers have found that the value and type of relationships with network members may be associated more with support than the number of network members (Reich et al 2010;Rock Wohl et al 2010). An increase in the number of individuals who made participants feel loved was associated with less fear of disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence of its beneficial effects for a wide variety of health outcomes (Gottlieb & Bergen, 2010; Heaney & Israel, 2008), and the field of public health now recognizes social support as an important determinant of health, particularly as it may interact with other social characteristics such as socio-economic position and social integration (Grundy & Sloggett, 2003; Stansfeld, 2006; Weyers et al, 2008). Social support may buffer some of the disadvantages faced by sexual and gender minority Latinos; however, research to-date has largely been restricted to HIV-related topics (Carlos et al, 2010; Fekete et al, 2009; Wohl et al, 2010; Zea, Reisen, Poppen, Bianchi, & Echeverry, 2005). This reflects the preponderance of research on sexual behavior and relatively scant attention to the relationship between social support and other risky behaviors, including substance use, among this sub-group of Latinos.…”
Section: Introductionmentioning
confidence: 99%